Synergizing pico hydel and battery energy storage with adaptive synchronverter control for frequency regulation of autonomous microgrids - Vasudevan K.R.; Ramachandaramurthy V.K.; Venugopal G.; Guerrero J.M.; David Agundis Tinajero G. (Elsevier Ltd, 2023)
Adaptive control systems; Computer circuits; Deterioration; Eigenvalues and eigenfunctions; Electric batteries; Fuzzy logic; Renewable energy resources; Synchronous generators; System stability; Autonomous microgrids; Frequency regulations; Fuzzy-Logic; Hybrid energy storage; Microgrid; Pico-hydel; Pumped hydro storage; Synchronverte; System inertia; Virtual synchronoi generator; MATLAB; damping; eigenvalue; energy storage; fuzzy mathematics; machinery; optimization